Dampak Krisis Sub-Prime Mortgage Terhadap Ekonomi Makro Dan Pasar Modal di Indonesia - Husein Umar (JRB-Jurnal Riset Bisnis, 2017)
The research aimed to find the relationship among customer price index, exchange rate, the world price of oil and mining sector index as a result of the subprime mortgage crisis, and to determine the impact of the sub-prime mortgage crisis on the relationship among macro economic variables. The data used in the period January 2000 to April 2013. The analytical tool used are the Vector Autoregression (VAR), impulse response function (IRF) and variance decomposition (VD). This study found that 1) there is a relationship among customer price index, exchange rate, the world price of oil and mining sector index, but no cointergation among them, 2) there is an impact of sub-prime mortgage crisis on relationship among macro economic variables examined.